BELARUSIAN LEXICOGRAPHICAL CODIFICATION OF THE FIRST HALF OF THE 20TH CENTURY AND “DICTIONARY OF THE UKRAINIAN LANGUAGE” EDITED BY B. GRINCHENKO: SPECIFICITY OF DESCRIPTIVE METHODS - Скопненко, О. І. (Studia Philologica, 2019)
The article in a comparative aspect describes the main prescriptive methods of the “Dictionary of the Ukrainian language” edited by Borys Grinchenko (1907–1909) and the most well-known codes of the new Belarusian literary language of the first half of the 20th century: “Belarusian-Russian Dictionary” by M. Baikov and S. Nekrashevich (1925) and “Russian-Belarusian Dictionary” by S. Nekrashevich and M. Baikov (1928). It is stated that the “Dictionary of the Ukrainian language” edited by Borys Grinchenko differs in his prescriptive methods from the Belarusian codes under consideration, in many respects it is more thoroughly and thoroughly thought out. In the dictionary edited by Borys Grinchenko describes the variability and synonymy of units better than in the considered Belarusian ones. Comparison of the specifics of the descriptions of the Ukrainian and Belarusian dictionaries of the 20th century will help identify the characteristic features of the tradition of lexicographical description of vocabulary in two national schools, show ways of establishing prescriptive linguistics of Belarus and Ukraine in the specified period.